1991
DOI: 10.1111/j.1476-5381.1991.tb12261.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of p‐chlorophenylalanine on release of 5‐hydroxytryptamine from the rat frontal cortex in vivo

Abstract: 1 Rats were given p-chlorophenylalanine (PCPA, 150mgkg-1, i.p.) to inhibit partially 5-hydroxytryptamine (5-HT) synthesis so that its concentration in the frontal cortex fell by about half. The effects of this treatment on frontal cortex dialysate 5-HT and 5-hydroxyindoleacetic acid (5-HIAA) concentrations were determined before and after stimulation by increasing K+ concentration in the perfusion fluid by 100 mm for 20 min. Rates of 5-HT synthesis as indicated by the effects of 3-hydroxybenzylhydrazine (NSD 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 20 publications
3
5
0
1
Order By: Relevance
“…Our data from the pig brain are in line with similar studies in rats where pCPA is found to effectively and selectively decrease 5-HT and 5-HIAA tissue concentrations (Koe and Weissman, 1966;Kornum et al, 2006;O'Connell et al, 1991). The higher percentages of serotonin depletion (>90%) achieved in rats are likely to be explained by the higher doses of pCPA (250-400 mg/kg) and perhaps also by the route of administration (intraperitoneal vs. intramuscular) (Kornum et al, 2006;O'Leary et al, 2007;Paxinos et al, 1977), and furthermore, 100 mg/kg pCPA given to rats only resulted in 30% cortical serotonin depletion (Datla and Curzon, 1996).…”
Section: Discussionsupporting
confidence: 89%
“…Our data from the pig brain are in line with similar studies in rats where pCPA is found to effectively and selectively decrease 5-HT and 5-HIAA tissue concentrations (Koe and Weissman, 1966;Kornum et al, 2006;O'Connell et al, 1991). The higher percentages of serotonin depletion (>90%) achieved in rats are likely to be explained by the higher doses of pCPA (250-400 mg/kg) and perhaps also by the route of administration (intraperitoneal vs. intramuscular) (Kornum et al, 2006;O'Leary et al, 2007;Paxinos et al, 1977), and furthermore, 100 mg/kg pCPA given to rats only resulted in 30% cortical serotonin depletion (Datla and Curzon, 1996).…”
Section: Discussionsupporting
confidence: 89%
“…They were stored at Ϫ80°C for 2 d. On the day of analysis, the supernatants were thawed and mixed with 3,4-dihydroxybenzylamine as an internal standard. Levels of dopamine, homovanillic acid, and 5-hydroxytryptamine (5-HT) were determined by HPLC combined with electrochemical detection, as described previously (O'Connell et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…As availability of 5-HT for release falls in proportion with its depletion by pCPA (O'Connell et al, 1991), a hypothermic effect of 5-HTIA agonists due to decreased release at axon terminals following activation of presynaptic receptors would be unlikely to survive the above pCPA treatments. Incidentally, Satinoff et al (1991) found that pCPA was acutely hypothermic but, in agreement with our findings, temperature was normal on the day after injection.…”
Section: First Injectionmentioning
confidence: 99%